2012
DOI: 10.1097/iop.0b013e3182696552
|View full text |Cite
|
Sign up to set email alerts
|

Periocular Abscesses Following Brow Epilation

Abstract: Periocular abscess formation after brow epilation has been previously described in only a single case report in the literature. The authors believe this entity is underreported given their current report describing 26 such cases. Given the high prevalence of cosmetic brow epilation in females, the authors believe a careful history regarding brow epilation in any patient presenting with a periocular abscess or preseptal cellulitis is essential to explore the possible cause of their infection. The majority of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…6 Abscess formation at the site of plucking has been reported in rare cases, as evidenced by a retrospective study that documented cases of methicillin-sensitive/resistant staphylococcus aureus (MSSA/ MRSA) abscesses in adolescents following brow plucking. 31 Another case study reported two cases of verruca plana in adults following threading at a salon. 32 One case was theorized to be koebnerized spread from an active lesion at a distant site, while the other was theorized to be virally transmitted from the provider.…”
Section: Threading/pluckingmentioning
confidence: 99%
“…6 Abscess formation at the site of plucking has been reported in rare cases, as evidenced by a retrospective study that documented cases of methicillin-sensitive/resistant staphylococcus aureus (MSSA/ MRSA) abscesses in adolescents following brow plucking. 31 Another case study reported two cases of verruca plana in adults following threading at a salon. 32 One case was theorized to be koebnerized spread from an active lesion at a distant site, while the other was theorized to be virally transmitted from the provider.…”
Section: Threading/pluckingmentioning
confidence: 99%
“…Furthermore, it was discovered that after waxing, the beautician would check for remaining hairs on the waxed skin using her bare hands, which she did not wash after removing her gloves. Elmann et al (2012) evaluated a cohort of 26 female cases of periocular abscess, an inflamed mass containing pus around the eye, following after recent brow epilation (waxing and plucking). Results indicated that these women had acquired infections of methicillin resistant or sensitive S. aureus.…”
Section: Review Of Reported Infectionsmentioning
confidence: 99%
“…As the Netherlands outbreak highlights, infected estheticians and clients can act as (unknowing and asymptomatic) reservoirs and sources of infection if they practice poor personal hygiene (Huijsdens et al, 2008). Surfaces in the salon may be contaminated and improperly disinfected (Fritz, 2008;Elmann 2012). The source of infection can also be the associated equipment and products such as the wax, applicators, cloth strips, tweezers or cream which have been cross-contaminated through the re-use between clients or with the same client (auto-infection).…”
Section: Review Of Reported Infectionsmentioning
confidence: 99%
“…Recent reports in the last decade on endophthalmitis or postoperative infection include small retrospective cases series or case reports following cataract surgery [65,70,83,98], after amniotic membrane transplantation [64], following scleral buckle placement [68], following PK [69], following Ahmed valve placement [71], and after cornea refractive surgery [77][78][79][80][81][82][83][84]. Other reports are frequently site-specific, including orbital cellulitis [99][100][101][102][103][104], lacrimal system involvement [91,[105][106][107], and, most recently, after brow epilation [108].…”
Section: Spectrum Of Eye Diseasementioning
confidence: 99%